Phreatomagmatic activity and associated hydrothermal processes in the lamproitic Volcano of Cancarix (Southeast Spain) - Reolid, Matias; Abad, Isabel; Sanchez-Gomez, Mario (Journal of Iberian Geology, 2015)
The study of the Cancarix volcano structure (Sierra de las Cabras, SE Spain) and the regional observations in similar lamproite volcanoes suggest that these magmas were emplaced during the Miocene in relation to transtensive structures at the North end of the Betic Cordillera. These structures were able to reactivate previous basement faults which facilitated the ascending circulation of enriched ultrapotassic magma. Two episodes are distinguished: 1) explosive volcanism due to the interaction between magma and groundwater from the karstic system of the host carbonate rocks, which generated a phreatomagmatic-effusive complex and 2) volcanic-building with crystal-rich magma. The phreatomagmatic breccia distribution is conditioned by the tectonic structure of the host rock, with maximum thickness over the marls basement, mechanically less competent, which is controlling the preferential magma movement towards the S-SE. Chemical, mineralogical and textural study of the host rocks and the volcanic products indicates that following the magmatic activity hydrothermal processes ocurred, with: (1) the genesis of new minerals (namely, saponitic smectite and serpentine minerals) in the host rock clasts from the phreatomagmatic breccia; and (2) the recrystallisation of dolomite and amorphous silica growing up to 20 m from the contact in porous carbonates. In contrast, marls and micritic carbonates show no recrystallisation, only a slight enrichment of Mg and some exotic elements, limited to the first few metres.